2022
DOI: 10.1039/d2ja00116k
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle identification using single particle ICP-ToF-MS acquisition coupled to cluster analysis. From engineered to natural nanoparticles

Abstract: In this study, mono-, bi-, and tri-metallic engineered nanoparticles (ENPs) are first analysed using an ICP-ToF-MS in single particle mode. The method is also used to characterize natural NPs (NNPs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The emerging growth in the development, production, and application of multi-element engineered NPs (ENPs), which are widely incorporated into commercial products, requires advanced analytical methods which allow for size fractionation and chemical quantification of nanomaterials [72,73]. Some of the published studies regarding determination of the elemental and isotopic composition of NPs are summarized in Table 3.…”
Section: Determination Of the Elemental And Isotopic Composition Of Npsmentioning
confidence: 99%
See 2 more Smart Citations
“…The emerging growth in the development, production, and application of multi-element engineered NPs (ENPs), which are widely incorporated into commercial products, requires advanced analytical methods which allow for size fractionation and chemical quantification of nanomaterials [72,73]. Some of the published studies regarding determination of the elemental and isotopic composition of NPs are summarized in Table 3.…”
Section: Determination Of the Elemental And Isotopic Composition Of Npsmentioning
confidence: 99%
“…SP-ICP-MS technique enables rapid measurements of size, mass, concentration, and element/isotope concentration. However, the monitoring of multiple elements in an individual NP in a single run is not possible [4,72,78]. Although the increase in acquisition time and peak-jumping enables for multi-element analysis of single particle to some extent, it was observed that the multiple detection is still limited to at most two targeted elements in each NP [69].…”
Section: Determination Of the Elemental And Isotopic Composition Of Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a drawback, the analysis of elements from the lower mass range with biological key functions is not possible with this kind of instrumentation. There are currently different ICP-TOFMS systems on the market that provide the capability to measure m / z = 14–256 and, therefore, imaging of endogenous elements at the cellular level . Several LA-ICPMS studies employed quadrupole-based ICP–MS systems, limiting the number of elements that can be measured simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…21 Examples of supervised learning methods used for NP and mP classication from spICP-TOFMS datasets include gradient boosted classiers (GBC), 32 light-GBC, 21 k-nearest neighbor embedding (KNN), 35 and binomial logistic regression (LR). 19 Unsupervised approaches, such as clustering analysis 20,33,34,39 or t-stochastic neighbor embedding, 21 have also been reported for NP classi-cation from spICP-TOFMS datasets.…”
Section: Introductionmentioning
confidence: 99%